Transcutaneous Bilirubin Measurement as a Predictor of Significant Neonatal Hyperbilirubinemia in Low Birth Weight Neonates - S Rao, Suchetha; Chellaganapathy, Karthik; Kamath, Nutan (Journal of Nepal Paediatric Society, 2022)
Introduction: Early recognition of neonatal hyperbilirubinemia is essential to prevent bilirubin encephalopathy. Transcutaneous bilirubin (TCB) measurement is a simple and easy method to predict neonatal hyperbilirubinemia. We aimed to study the efficacy of TCB as a predictor of subsequent significant neonatal hyperbilirubinemia in low birth neonates and compared the forehead and sternal sites for TCB measurement. Methods: A prospective study was conducted from August to October 2018 at a teaching hospital in South India including term and late preterm neonates weighing < 2.5 kg. The TCB values were obtained from the forehead (TCB-FH) and sternum (TCB-S) by a non-Invasive Bilirubin Analyser. The average of TCB (TCB- AV) was determined for each baby with TCB-FH and TCB –S values. Neonates were followed up subsequently till discharge for the development of significant hyperbilirubinemia. Receiver operating characteristic (ROC) curve was generated and the best cut-off value for 24-hour TCB as a predictor of significant hyperbilirubinemia was established. Results: The study included 88 neonates, of which 39 (44.3%) were late preterm and 49 (55.7%) term small for gestation age. Mean values of TCB –AV 6.25 ± 1.58, TCB – FH 6.24 ± 1.57391, and TCB – S 6.27 ± 1.56 were noted. The cut off value for TCB – AV was found to be 6.85 as a predictor for subsequent neonatal hyperbilirubinemia. TCB – AV was a better predictor than TCB - FH or TCB – S. Conclusions: TCB measurement is an easy and reliable predictor for subsequent significant hyperbilirubinemia in low birth weight neonates. The average of TCB forehead and sternum was a better predictor of significant hyperbilirubinemia.